The threat of Chikungunya in Oceania - Horwood, Paul Francis; Bande, Grace; Dagina, Rosheila; Guillaumot, Laurent; Aaskov, John; Pavlin, Boris (Western Pacific Surveillance and Response, 2013)
Not applicable (Perspectives article)